Ornidazole-loaded graphene paper for combined antibacterial materials - Wenhao Qian; Zhaolei Wang; Dannong He; Xiaoyu Huang; Jiansheng Su (Journal of Saudi Chemical Society, 2018)
Excellent antibacterial property of graphene oxide makes it an important antibacterial material. However, in some cases, a synergistic combination of materials with different antibacterial mechanisms is desired. In this work, we developed a simple two-step protocol to prepare ornidazole (ONZ), a nitroimidazole antiprotozoal drug, loaded graphene-based paper for combined antibacterial materials. Graphene oxide (GO) and reduced graphene oxide (rGO) were used as carriers in antibacterial materials. After mixed with ONZ directly in aqueous media and filtrated under vacuum, the freestanding GO/ONZ and rGO/ONZ were peeled off from the filtrate membrane. The ONZ loading contents in the paper was determined by UV/vis spectroscopy and the surface properties were investigated by measuring their contact angle, which will have an important impact on the antibacterial effects of the papers. Keywords: Ornidazole, Graphene oxide, Antibacterial material